Demografía y cambio ambiental. Hipótesis para el cambio económico en el Cantábrico Oriental durante el Tardiglacial - Marín Arroyo, Ana Belén (Complutum, 2008)
The zooarchaeological record available in Eastern Cantabrian sites during the Late Glacial shows clear evidences of a gradual economic change from specialized hunting strategies to more diversified ones, in a progressive trend towards an ecological niche enlargement. However, there is not a general agreement on the causes that triggered this evolution, with two main opposite points of view: a demographic theory, which proposes a continuous growth of human population and its energetic requirements as the determining factor, and an environmental one, which establishes the improvement of the climate and the reforestation as precursor elements. In this paper, the question is assessed by building a mathematical model that simulates the relationship between the biological cycle of some ungulates and the human hunting, finally establishing the demographic hypothesis as the most likely one.